Luxury Brand Equity Strategy: Market Segmentation and Luxury Dimensions in International Business - Klomtooksing, Warisara (Journal of Dhamma for Life, 2024)
This academic article aims to study the creation of brand value in the luxury level, its connection with luxury market segmentation, luxury level, and international business theory. This is documentary research to analyze the differences between domestic and international markets through the CAGE Distance Framework theory, which reflects the differences between consumers in the Western market and the Asian market. It is a factor that luxury brands should emphasize the uniqueness and quality of luxury products sold to consumers in the Western market to be consistent with the culture of individualism. Meanwhile, the Asian market, which purchases luxury products to show social status, should emphasize the clear display of the luxury brand logo and its use in seeking acceptance from other social classes following the culture of collectivism.